Intrinsic determinants and predictors of superovulatory yields in sheep: Circulating concentrations of reproductive hormones, ovarian status, and antral follicular blood flow - Bartlewski, Pawel M.; Seaton, Patricia; Franco Oliveira, Maria Emilia [UNESP]; Kridli, Rami T.; Murawski, Maciej; Schwarz, Tomasz (Elsevier B.V., 2016)
Hormonal ovarian superstimulation has contributed to small ruminant reproduction around the world, impacting genetic improvement and zoosanitary programs, contributing to the conservation of endangered species, and supporting other related biotechnologies. Advanced knowledge surrounding the superovulatory treatments in sheep has resulted in enhanced control of influencing factors and improved the protocols currently used. However, in spite of minimization of some adverse factors, superovulatory responses in ewes still remain variable, preventing the more widespread use of superovulation in commercial embryo transfer programs and reproductive research in this species. Recent evidence demonstrates that changes in antral follicular populations and blood supply, and circulating concentrations of certain reproductive hormones determined at the specific time points just before or during the superovulatory treatment are associated with superovulation success in ewes. This review attempts to compile the data from available literature to identify ovarian and hormonal determinants of the superovulatory outcome in ewes, which can be used to substantially improve the existing protocols and to reduce the extra cost and unnecessary stress imposed on poorly responding animals. An overview of most commonly used and some recently developed, FSH-based ovarian stimulation protocols is given at the outset to highlight variation in the frequency and timing of gonadotropin injections, estrus synchronization methods, and follicular wave synchronization and/or ovulation induction techniques during the superovulatory treatments in ewes. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Ewe; Superovulation; Ovarian follicles; Blood flow; Steroids; Gonadotropins